The Effect of Psychosocial Stress on the Incidence of Hypertension in Rural and Urban Communities - Mira Istiana; Yeni Yeni (Media Kesehatan Masyarakat Indonesia, 2019)
The prevalence of hypertension in Indonesia increased to 34.1% in 2018. Hypertension incidence was higher in rural than urban. Psychosocial stress was hypertension risk factors. Individuals with psychosocial stress 3 times at risk get hypertension. The purpose was to determine effect of psychosocial stress on hypertension in rural and urban communities. A cross sectional study design with secondary data IFLS 5 in 2014. Sample was respondents of IFLS 5 who ≥15 years old and had blood pressure measurement data. The sample size was 10.008 in rural and 16,057 urban. Data analysis use complex sample as secondary data analysis technique by considering weighting when analyzing data. The results showed the hypertension was 29.7% in rural and 31.3% in urban. In rural, psychosocial stress increases the risk of hypertension after being controlled for age, sex, education, economic, marital status and BMI (PR = 1,108; 95% CI = 1,016-1,209). In urban, psychosocial stress increases the risk of hypertension after being controlled by age, sex, education, economic, marital status, BMI and tobacco consumption (PR=1,174; 95% CI=1,032-1,335). Psychosocial stress was a risk factor for hypertension. The importance of providing hypertension prevention education such as stress management techniques to prevent hypertension in integrated assistance post (Posbindu).